Evaluación digital del aprendizaje en los estudiantes con necesidades educativas de Educación General Básica Superior - Arias Duque, Enma Marina (2023)
Digital assessment is a process that utilizes technological tools to measure student performance in a particular subject area. These tools may include online exams, formative assessments, and automated grading software, among others, tailored to a specific classroom environment. It is an effective teaching and learning method to ensure students have the necessary skills and knowledge to reach their full potential. Utilizing assessment platforms can monitor student progress, with automatic grading. Platforms like Google Forms, Kahoot, Quizizz, and Google Classroom allow for efficient questionnaires and exams, with frequent feedback on performance being both constructive and encouraging.............